2018
DOI: 10.1021/acs.langmuir.7b03465
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fluorescence Quenching Ability of Graphene Oxide with a Layer of Rigid and Tunable Silica Spacer

Abstract: The fluorescence quenching property of graphene oxide (GO) has been newly demonstrated and applied for fluorescence imaging and biosensing. In this work, a new nanostructure was designed for effectively studying the quenching ability of GO. The key element in this design is the fabrication of a layer of rigid and thickness adjustable silica spacer for manipulating the distance between the GO and fluorophores. First, a silica core modified with organic dye molecules was prepared, followed by the formation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…The presence of a stable interaction between the targeting module Pyr-RF and the GQD surface was also proved by evaluating the fluorescence properties of GQD@Pyr-RF and GQD-PEG-BFG@Pyr-RF and comparing their PL spectra with those of GQD and of the unbound Pyr-RF samples at the excitation wavelength of 360 (Figure 4). As reported, some small molecules exhibit fluorescence quenching ability after their π–π stacking with the surface of graphene-based materials [41]. The PL spectra of the GQD-based samples conjugated with the Pyr-RF module reveal a quenching phenomenon of the vitamin fluorescence, which is ascribable to an electron transfer process triggered by π–π stacking interactions between the aromatic rings of RF and the p-cloud of GQD.…”
Section: Resultsmentioning
confidence: 78%
“…The presence of a stable interaction between the targeting module Pyr-RF and the GQD surface was also proved by evaluating the fluorescence properties of GQD@Pyr-RF and GQD-PEG-BFG@Pyr-RF and comparing their PL spectra with those of GQD and of the unbound Pyr-RF samples at the excitation wavelength of 360 (Figure 4). As reported, some small molecules exhibit fluorescence quenching ability after their π–π stacking with the surface of graphene-based materials [41]. The PL spectra of the GQD-based samples conjugated with the Pyr-RF module reveal a quenching phenomenon of the vitamin fluorescence, which is ascribable to an electron transfer process triggered by π–π stacking interactions between the aromatic rings of RF and the p-cloud of GQD.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, graphene-based nanomaterial can act as a quencher in the transducer to generate fluorescent biosensors. Studies have determined that graphene (G), graphene oxide (GO), and reduced graphene oxide (rGO) have a very high efficiency of fluorescent quenching [ 20 22 ].…”
Section: Graphene-based Nanomaterials As a Biosensormentioning
confidence: 99%
“…The quenching could be due to the energy transfer from the fluorophore to the metal [42] or in the case of graphenes, it could be due to the excitation of an exciton too [43]. Wu et al found that the quenching efficiency of GO was still around 30% when the distance between dyes and GO was increased to more than 30 nm [44].…”
Section: Determination Of Human Cancer Cell Line A549 Response To Go mentioning
confidence: 99%